15th nordic-baltic conference on biomedical engineering and medical physics (NBC 2011) 14-17 June 2011, Aalborg, Denmark - Dremstrup, Kim; Rees, Steve; Jensen, Morten Olgaard (IFMBEpProceedings, 2011)
This volume presents the Proceedings of the 15th Nordic-Baltic Conference on Biomedical Engineering and Medical Physics. NBC 2011 brought together science, education and business under the motto Cooperation for health. The topics covered by the Conference Proceedings include: Imaging, Biomechanics, Neural engineering, Sport Science, Cardio-pulmonary engineering, Medical Informatics, Ultrasound, Assistive Technology, Telemedicine, and General Biomedical Engineering.